Resposta dos tecidos periodontais e peri-implantares à abordagens protéticas com e sem terminação de margem cervical: revisão sistemática da literatura - Merchan, Karina Victoria Espinoza (2022)
Prostheses with defective margins can contribute to the progression of periodontal diseases. There is no consensus in the literature that defines which type of finish line should be selected when placing a subgingival margin. In recent years, the Biologically Oriented Preparation Technique (BOPT) has generated much interest in clinicians, due to the results achieved in both prosthetic and periodontal conditions. The purpose of this systematic review was to evaluate the response of periodontal and peri-implant tissues to prosthetic approaches with and without a cervical finish line in teeth and dental implant abutments. An electronic search was performed in six databases and complemented by a manual search and in the gray literature. Regarding tooth preparation with and without finish line, 7 studies out of 1388 identified were included in the systematic review, and only 2 in the meta-analysis. In the meta-analysis, when analyzing the gingival index, no significant difference was observed when the two termination lines were compared (OR = 1.05 [95%CI: 0.35, 3.11]). Regarding implant abutments with and without cervical finish line, 6 studies out of 707 identified were included in the systematic review, and only 2 in the meta-analysis. The meta-analysis shows a trend towards lower marginal bone loss (MD = -0.54 [95% CI: -1.60, 0.52]) and lower probing depth levels (MD = -0.27 [95% CI: -0.83, 0.29]) when using abutments without end cervical, however there was no significant difference between the two types of implant abutments. It is concluded that, in test and control situations, no significant difference was identified between the prosthetic approaches with and without cervical finish line. The existence of few randomized controlled clinical trials that evaluate prosthetic approaches without finish line makes it difficult to obtain conclusive results regarding the real benefits on periodontal tissues.